INDIGENOUS TREES INVENTORY AND THEIR MULTIPURPOSE USES IN DUTSIN-MA AREA KATSINA STATE - Rabi’u Tukur; Garba K/Naisa Adamu; Ibrahim Abdulrashid; Murtala Rabi’u (European Scientific Journal, ESJ, 2013)
Indigenous trees are of high value among rural dwellers in Katsina State as indicated by many research findings. This research paper is aimed at assessing multi-purpose use of indigenous trees around Dutsin-ma area of Katsina State. An inventory of the trees is taken and multi-purpose use and access rights of the trees analyzed. The research identified seventy five (75) numbers of indigenous trees. It found that indigenous trees in the area play vital role on the socioeconomic development of the people and this has made it possible for the people to undergo various trading activities of some useful parts of the trees. The research recommends sustainable use of the resource through researches to explore more potential uses, and indiscriminate felling should be discouraged or stopped.